2022
DOI: 10.1055/s-0041-1742178
|View full text |Cite
|
Sign up to set email alerts
|

Manual Reduction of Incarcerated Abdominal Wall Hernias. A Feasible Option during COVID-19 Pandemic: A Prospective Study

Abstract: Background Incarcerated hernia is a common surgical emergency with considerable morbidity or even mortality. Manual reduction (taxis) and elective surgery could be an alternative management approach. This study examines the role of taxis with the adjuvant use of the visual analogue scale (VAS) score in treating incarcerated hernias and thereby decreasing the emergency surgery rate, especially during the novel coronavirus disease 2019 (COVID-19) pandemic. Methods All adult patients admitted to the eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Four studies described the impact of the timing of emergency umbilical hernia repair 2 , 7 , 14 , 16 . Two were retrospective cohort studies from national databases 2 , 14 and two were small single-centre studies 7 , 16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies described the impact of the timing of emergency umbilical hernia repair 2 , 7 , 14 , 16 . Two were retrospective cohort studies from national databases 2 , 14 and two were small single-centre studies 7 , 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies described the impact of the timing of emergency umbilical hernia repair 2 , 7 , 14 , 16 . Two were retrospective cohort studies from national databases 2 , 14 and two were small single-centre studies 7 , 16 . A study of the NSQIP database found that, despite overall increased odds of a major complication with next-day surgery for all emergency hernia presentations, multivariable logistic regression for next-day umbilical hernia surgery was associated with decreased odds of a major complication compared to surgery delayed more than one day 2 .…”
Section: Resultsmentioning
confidence: 99%
“…13 It was reported, at last, that the VAS score could add important findings to evaluate the persistence of pain even after a positive Taxis maneuver. 14 In view of the reimbursement provided to our hospital by the Italian National Health Service, in reference to inguinal hernioplasties, it has been used a standardized table costs format which unfortunately appeared to be poorly correlated with the overall unpredictability and also with the rising costs during the pandemic, especially when surgical interventions in urgent settings were performed. In the present study, we roughly estimated that, for inguinal hernioplasties carried out in this hospital, the total net national tablebased reimbursement, during the pre-pandemic, amounted to 146,432 Euros for day surgeries, to 60,211 Euros for outpatients and 143,483 Euros for inpatients, meanwhile during the pandemic amounted to 81,920 Euros for day surgeries, to 20,070 Euros for outpatients, and 216,974 Euros for inpatients, respectively: in particular, we inferred that the higher costs incurred for the inpatients during the pandemic are due to an increased number of urgent surgeries including, in most of the cases, complications of delayed elective surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was suggested that the only chance to correctly diagnose a hernia with strangulation rather than incarceration is to perform a CT scan, but likely this strategy would not be economically feasible 13 . It was reported, at last, that the VAS score could add important findings to evaluate the persistence of pain even after a positive Taxis maneuver 14 …”
Section: Discussionmentioning
confidence: 99%
“…The significant delay between the patient's arrival and clinical presentation of symptoms has also been reported in another emergency department due to the fear of developing hospital-acquired infection and the lack of medical supplies [ 21 , 22 ]. It has been estimated this delay could lead to more severe outcomes, such as the development of gallbladder spillage or rupture [ 23 - 25 ].…”
Section: Discussionmentioning
confidence: 99%